2016
DOI: 10.18632/oncotarget.14079
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus-associated intrahepatic cholangiocarcinoma: a malignancy of distinctive characteristics between hepatocellular carcinoma and intrahepatic cholangiocarcinoma

Abstract: It has been a decade since hepatitis B virus infection was identified as an etiological factor for the development of intrahepatic cholangiocarcinoma (ICC). In recent years, several studies have elucidated the critical impact of hepatitis B virus in ICC that significantly influenced the clinicopathological characteristics of ICC patients with intrahepatic cholangiocarcinoma. Distinctive features of patients with hepatitis B virus-associated ICC included younger age, preponderance of male patients, frequent ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Recent epidemiological studies reported hepatitis B virus infection as a risk factor of intrahepatic cholangiocarcinoma [40,41] . Intrahepatic cholangiocarcinoma patients with current and past hepatitis B virus infection were reported to display a better prognosis as compared with those without a history of hepatitis B virus infection [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies reported hepatitis B virus infection as a risk factor of intrahepatic cholangiocarcinoma [40,41] . Intrahepatic cholangiocarcinoma patients with current and past hepatitis B virus infection were reported to display a better prognosis as compared with those without a history of hepatitis B virus infection [42] .…”
Section: Discussionmentioning
confidence: 99%
“…According to one of our previous studies, HBV-associated ICC demonstrated distinctive clinical, pathological, and prognostic characteristics compared to ICC without HBV infection. HBV-associated ICC demonstrated relatively younger age, high male distribution, high incidence of cirrhosis and tumor encapsulation, poor tumor differentiation, infrequent lymph node metastasis, low seropositivity for CA19-9, frequent elevation of serum AFP and aspartate transaminase, longer prothrombin time, and frequent microvascular invasion 4 . In addition, we most recently confirmed that the presence of HBV infection is a favorable prognostic factor that significantly reduced recurrence rate after hepatic resection and the application of HBV infection could acceptably predict the RFS (concordance index: 0.65) in patients with ICC 23 .…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study and recent findings, HBV-associated ICC has been found to be a distinct entity with different clinicopathological and biological characteristics, such as younger aged, relatively infrequent incidence of lymph node metastasis, elevated serum aspartate transaminase and alpha fetoprotein (AFP), relatively lower level of serum carbohydrate antigen 19-9 (CA19-9), and prolonged survival outcomes 4 . However, to our knowledge, there is no such therapeutic approach that is specifically indicated for this group of patients.…”
Section: Introductionmentioning
confidence: 96%
“…ICCs arising from HBV infection hold approximately a half of all resected ICC cases in China and share common characteristics with hepatocellular carcinoma, including younger age and infrequent lymph node metastasis. (3,4) In addition, our recent study successfully and precisely predicts recurrence of ICC after hepatic resection by adding the presence of HBV infection as a favorable prognostic factor (C-index, 0.65; 95% confidence interval, 0.50-0.64). (5) Furthermore, we would like to point out results from our most recent study that showed surprising overall survival (1year, 88.9%; 3-year, 77.8%; 5-year, 66.7%) of patients with HBV-associated ICC who underwent hepatic resection and postoperative transarterial chemoembolization (TACE).Because the study reporting the most favorable outcome that was found in patients with a single tumor of <2 cm (1-year, 93%; 3-year, 84%; 5-year, 65%) from Sapisochin et al (6) is comparable to patients with ICC arising from HBV infection who underwent hepatic resection and postoperative TACE, future large-sized clinical trials need to evaluate the role of combined LT and postoperative TACE treatment in patients with ICC arising from HBV infection to potentially expand the inclusion criteria of LT for ICC.…”
mentioning
confidence: 98%
“…ICCs arising from HBV infection hold approximately a half of all resected ICC cases in China and share common characteristics with hepatocellular carcinoma, including younger age and infrequent lymph node metastasis. (3,4) In addition, our recent study successfully and precisely predicts recurrence of ICC after hepatic resection by adding the presence of HBV infection as a favorable prognostic factor (C-index, 0.65; 95% confidence interval, 0.50-0.64). (5) Furthermore, we would like to point out results from our most recent study that showed surprising overall survival (1year, 88.9%; 3-year, 77.8%; 5-year, 66.7%) of patients with HBV-associated ICC who underwent hepatic resection and postoperative transarterial chemoembolization (TACE).…”
mentioning
confidence: 98%